2009
DOI: 10.1111/j.1582-4934.2009.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Moesin Dependent Cytoskeleton Remodeling Is Associated With an Anaplastic Phenotype of Pancreatic Cancer

Abstract: Cell motility is controlled by the dynamic cytoskeleton and its related proteins, such as members of the ezrin/radixin/moesin (ERM) family, which act as signalling molecules inducing cytoskeleton remodelling. Although ERM proteins have been identified as important factors in various malignancies, functional redundancy between these proteins has hindered the dissection of their individual contribution. The aim of the present study was to analyse the functional role of moesin in pancreatic malignancies. Cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 35 publications
0
33
0
1
Order By: Relevance
“…As shown by other studies (41,42), phosphorylation of ERM proteins is an important regulatory mechanism that has been related to cell motility, migration, and cell invasion. We found that SL are not just involved in ERM inactivation but are also involved in a rapid activation driven by S1P.…”
Section: Discussionmentioning
confidence: 61%
“…As shown by other studies (41,42), phosphorylation of ERM proteins is an important regulatory mechanism that has been related to cell motility, migration, and cell invasion. We found that SL are not just involved in ERM inactivation but are also involved in a rapid activation driven by S1P.…”
Section: Discussionmentioning
confidence: 61%
“…This transition is fundamental in tumour development and metastasis and allows epithelial cells to develop a mesenchymal and, therefore, more invasive phenotype. Moesin has been predicted to be a potential EMT marker in breast and pancreatic cancer (Abiatari et al, 2010;Haynes et al, 2011;Wang et al, 2012). Furthermore, expression profiles of both breast and basal breast carcinomas have shown strong upregulation of moesin (Charafe-Jauffret et al, 2007;Condeelis et al, 2005;Kobayashi et al, 2004;Wang et al, 2012).…”
Section: Moesinmentioning
confidence: 99%
“…Moesin expression has been associated with papillary thyroid carcinomas (Brown et al, 2006), oral squamous cell carcinomas (Kobayashi et al, 2004), basal breast carcinoma (Charafe-Jauffret et al, 2007), pancreatic cancer (Abiatari et al, 2010), colorectal carcinoma (Kim et al, 2012), and prostatic adenocarcinoma (Bartholow et al, 2011). In pancreatic adenocarcinoma, moesin-positive cases have been associated with shorter survival times than moesin-negative cases (Abiatari et al, 2010), with moesin-positive tumors showing higher histopathological grades and perineural and lymphovascular invasion rates (Torer et al, 2007). Our results indicated that 78.3% (47/60) of LSCC and 87.9% (29/33) of metastatic lymph nodes expressed high levels of moesin.…”
Section: Discussionmentioning
confidence: 99%